Evaluation of Groundwater Vulnerability in the Densu River Basin of Ghana - Anornu, G K; Kabo-bah, Amos Tiereyangn; Anim-Gyampo, M (American Journal of Human Ecology, 2012)
The paper evaluated the potential of groundwater pollution in the Densu River Basin of Ghana. Groundwater is an important resource in this basin currently supporting domestic, agricultural and industrial activities. The significance of water resources and the potential for groundwater quality to deteriorate due various anthropogenic activities within the Densu River Basin has necessitated this study using a combination of GIS and DRATIC methods. The study reveal that about 47% of the basin is exposed to high-risk, 43% exposed to medium-risk and 10% exposed to low-risk. It is recommended that the fast growing urban settlements in this high-risk prone areas need more careful urban planning of settlements, siting of irrigation schemes and sanitation facilities. The results in this research are replicable in other basins in Ghana and the sub-region.